2022
DOI: 10.1136/bmjopen-2021-057854
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analyses of sex/gender-related publication decisions in general medical journals: editorial rejection of population-based women’s reproductive physiology

Abstract: ObjectiveTo assess whether editorial desk rejection at general medical journals (without peer review) of two clinical research manuscripts may relate to author gender or women’s physiology topics. Given evidence for bias related to women in science and medicine, and editorial board attitudes, our hypothesis was that submissions by women authors, on women’s reproductive, non-disease topics received differential editorial assessment.DesignA prospective investigation of publications, author gender and topics in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Gender imbalance in the scientific publishing process is already evident when considering simple numerical disparities, starting with women’s representation in scientific editorial boards [ 67 73 ], number of invited articles [ 18 , 19 , 21 ], frequency of being asked to referee [ 75 77 ], published manuscripts’ topics [ 34 ], and number of publications [ 36 , 37 , 78 ]. Here we extend the scope of this disparity by reporting clear under-representation of women in the BRE of a prominent biomedical journal (eLife).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender imbalance in the scientific publishing process is already evident when considering simple numerical disparities, starting with women’s representation in scientific editorial boards [ 67 73 ], number of invited articles [ 18 , 19 , 21 ], frequency of being asked to referee [ 75 77 ], published manuscripts’ topics [ 34 ], and number of publications [ 36 , 37 , 78 ]. Here we extend the scope of this disparity by reporting clear under-representation of women in the BRE of a prominent biomedical journal (eLife).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific publishing is a central aspect of academia, with critical implications for hiring decisions and career advancement. Inequalities, based on an author’s gender, have been systematically documented along different stages of the scientific publishing process [ 4 , 20 , 32 34 ]. First, the proportion of women as first and senior authors in peer-reviewed publications is lower than expected given their prevalence in the field [ 4 , 20 , 35 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…As before, we continue to call on other journals to share their results on equity and diversity. We note that reports continue to be published demonstrating inequity in publishing and appear to be increasing in the years since we have been reporting RPTH data [ [7] , [8] , [9] ]. In one shocking example, considering Scopus-indexed medical journals published in Latin America, women comprised only 12.9% of those in editorial leadership positions [ 10 ].…”
Section: What Is Happening In the Literature?mentioning
confidence: 99%
“… 1 , 2 At the same time, there is an increasing awareness of the predominantly male-favored sex-bias across the fields in biomedical research. 3 , 4 Substantial evidence suggests that sexual dimorphism exists in the liver transcriptome across species—from zebrafish to human. 5 , 6 , 7 Various studies reported sexual dimorphism in liver gene expression—ranging from 40 to 50 genes to more than a half of liver transcriptome, depending on statistical power and magnitude of the difference.…”
Section: Introductionmentioning
confidence: 99%